Globalization and the International Law - Kamil A. Bekyashev (Московский журнал международного права, 2014)
The article suggests a deﬁ nition of globalization and considers its impact on the development International Law. The characteristics of the supremacy of International Law are also stated. Considered are series of new issues of International Law, generated by globalization: international protection of human rights, responsibility to protect, international legal prohibition of cyberattacks, conception of imminent armed attacks, legal force of the UN Security Council’ resolutions and other.